Young People's Aspirations in an Uncertain World: Taking Control of the Future?. (December 2022) - Ansell, Nicola; Froerer, Peggy; Huijsmans, Roy
The future for young people worldwide is characterised by multiple uncertainties, particularly perhaps in countries of the Global South. There is a growing and pervasive expectation that these uncertainties need to be responded to, both by institutions and individuals, so that young people are prepared for an unpredictable and changing world. 'Raising aspirations' is expected to play an instrumental role in preparing young people to confront a constantly changing world. Of the four articles that constitute this special section, two explore institutional efforts to shape young people's aspirations to build new kinds of (national and individual) future, while the other two focus on the messier, more fluid ways in which young people reorient themselves in relation to unpredictable events. Together, they highlight how interventions designed to produce flexible creative individuals largely ignore how young people already live their lives in responsive and creative ways.